American Community Survey (ACS): Public Use Microdata Sample (PUMS), 2006 ([Verlag nicht ermittelbar], 2008)
The American Community Survey (ACS) is a part of the Decennial Census Program, and is designed to produce critical information about the characteristics of local communities. The ACS publishes social, housing, and economic characteristics for demographic groups covering a broad spectrum of geographic areas in the United States and Puerto Rico. Every year the ACS supports the release of single-year estimates for geographic areas with populations of 65,000 or more. Demographic variables include sex, age, relationship, households by type, race, and Hispanic origin. Social characteristics variables include school enrollment, educational attainment, marital status, fertility, grandparents caring for children, veteran status, disability status, residence one year ago, place of birth, United States citizenship status, year of entry, world region of birth of foreign born, language spoken at home, and ancestry. Variables focusing on economic characteristics include employment status, commuting to work, occupation, industry, class of worker, income and benefits, and poverty status. Variables focusing on housing characteristics include occupancy, units in structure, year structure was built, number of rooms, number of bedrooms, housing tenure, year householder moved into unit, vehicles available, house heating fuel, utility costs, occupants per room, housing value, and mortgage status. The American Community Survey is conducted under the authority of Title 13, United States Code, Sections 141 and 193, and response is mandatory.